Doses of organomineral fertilizer in soybean - Ribeiro, M. E. G.; Pereira, C. S.; Fiorini, I. V. A.; Resende, F. R.; Silva, A. A.; Pereira, H. D. (Scientific Electronic Archives, 2020)
Organomineral fertilizers are the mixture of an organic fertilizer with an industrialized mineral fertilizer, they are fertilizers that activate the soil microbiota, provide nutrients and help retain moisture in the soil. The experiment was implemented at ConfianÃ§a I farm, in the city of Sorriso-MT. The objective of the work was to evaluate the productive performance of soybean when submitted to different doses of the organomineral fertilizer Green FactorÂ® in the presence or not of the organomineral fertilizer PT4-OÂ® in the dose 250 ml ha-1. The experimental design used was a randomized block design (DBC) in a 2x5 factorial scheme with 4 replications. The first factor was the presence or absence of â€œPT4-OÂ®â€, and the second factor is the different doses of Green FactorÂ® (0, 1, 2, 4 and 6 L ha-1). First, half of the seeds were treated with the product â€œPT4-OÂ®â€, starting from the recommended dose, while the other half did not receive any dose. Subsequently, soybean seeds were sown. At 25 days after emergence, doses of the product â€œGreen FactorÂ®â€ were applied to the plants. The parameters were quantified: leaf area, number of leaves, dry mass of the aerial part and grain yield. The data were submitted to statistical analysis, using the statistical software â€œSisvarÂ®â€. Through the obtained data, it was observed that: for all the evaluated characteristics in which there was interaction between the factors, the presence of PT4-OÂ® when associated with the dose of 6 liters per hectare of Green FactorÂ®, showed the highest values for the evaluated characteristics